Hubungan Kerapatan Mangrove Dengan Kepadatan Kepiting Bakau (Scylla spp.) Pada Kawasan Mangrove Pantai Kelapa Desa Tungkal I Tanjung Jabung Barat - Nurhasana, Qori; Gelis, Ester Restiana Endang; Heltri, Septy; Nurhayati, Nurhayati; Rolin, Febrina; Alwi, Yun (Jurnal Perikanan Unram, 2025)
This research was motivated by the ecological importance of mangrove ecosystems as natural habitats for mud crabs (Scylla spp.) and the suspected influence of mangrove density on the population of associated biota in the Mangrove Ecotourism Area of Pantai Kelapa, Tungkal I Village, West Tanjung Jabung. The main objectives of this study were to identify the types and density of mangroves, determine the species and density of mud crabs, analyze the relationship between mangrove density and mud crab density, and assess sediment composition. A descriptive analytical method was employed, using both primary and secondary data collection. The results revealed four species of mangroves (Sonneratia alba, Avicennia alba, Rhizophora mucronata, and Nypa fruticans) with total tree-level densities ranging from 366.66 to 766 individuals per hectare. Two species of mud crabs were identified (Scylla serrata and Scylla tranquebarica), with densities ranging from 200 to 566 individuals per hectare. The highest mud crab density was recorded at station 3, which also had the highest mangrove density. A simple linear regression analysis showed an R² value of 0.3226, indicating a weak correlation. These findings suggest that mangrove density has a limited and statistically insignificant influence on the density of mud crabs in the study area.